Analisis Persepsi Masyarakat Nagari Tandikek Utara Tentang Bantuan Pemerintah Selama Masa Pandemi Covid 19 - Amran, Elsa Fitri; Misharni, Misharni; Salfina, Lili; Syafriadi, Syafriadi; Amran, Sri Oktika (Jurnal Pendidikan Ekonomi (JUPE), 2022)
This study aims to analyze the perception of the people of Nagari North Tandikek about the subsidize provided by the government during the Covid 19 pandemic. The population in this study were people who received assistance from the government which consisted of assistance from the Social ministry of the republic Indonesia, West Sumatra Province, Padang Pariaman Regency, Nagari North Tandikek, and the Family Hope Program, which opened 617 people. The sample in this study found 123 people with a systematic sampling technique. This study uses a descriptive analysis method with a quantitative approach and the type of data in this study is primary data obtained from the collection of questionnaires using a Likert scale. The data analysis technique in this study is descriptive analysis of research variables seen from the average value (mean), standard deviation, maximum, minimum and the analysis of the level of achievement of respondents. The results of this study indicate the lowest public perception of 42.114% (Not Good) with indicators of community expectations with the assistance provided and the highest public perception of 62.602% (Less Good) with indicators of assistance that can improve the community’s economy. Meanwhile, the average perception of the people of Nagari Tandikek Utara towards the assistance provided by the government during the Covid-19 pandemic is very low or not good.